THE EFFECT OF ORGANIZATIONAL CULTURE, JOB SATISFACTION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. KOREA TOMORROW & GLOBAL INDONESIA ATTACK CITY - ANSORI; ELOH BAHIROH (PT Larva Wijaya Penerbit, 2022)
This research aims to analyze organizational culture , job satisfaction and work discipline on employee performance at PT. Korea Tomorrow & Global Indonesia Serang City . In this study there are four variables, namely organizational culture (X1), job satisfaction (X2), work discipline (X3), and employee performance (Y). This study involved all employees of PT. Korea Tomorrow & Global Indonesia Serang City as a sample of 61 employees. To get accurate results in this study using interviews, observations, and questionnaires this study uses descriptive methods, data analysis, instrument tests, classic assumption tests, determination coefficients, and t tests with calculations through SPSS version 26 . The results of this study show that: (1) Organizational Culture has a positive and significant effect on Employee Performance. (2) Job Satisfaction has a positive and significant effect on Employee Performance. (3) Work Discipline has a positive and significant effect on Employee Performance